2021
DOI: 10.1007/s00127-021-02099-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of suicide attempt and suicide in young adult refugees compared to their Swedish-born peers: a register-based cohort study

Abstract: Purpose Refugees, especially minors, who often have experienced traumatic events, are a vulnerable group regarding poor mental health. Little is known, however, of their risk of suicidal behaviour as young adults. We aimed to investigate the risk of suicidal behaviour for young adult refugees who migrated as minors. The moderating role of education and history of mental disorders in this association was also investigated. Methods In this register linkage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Studies exploring the relationship between trauma exposure and suicide risk among NK refugee women are limited. However, a few previous studies with other refugee populations have shown that higher levels of trauma can increase suicide risk (Ellis et al, 2015;Geirsdottir et al, 2021;Meyerhoff et al, 2018). According to the ITS (Joiner, 2005;Van Orden et al, 2010), not every individual with suicidal ideation acts on their suicidal thoughts.…”
Section: Exposure To Trauma and Suicide Riskmentioning
confidence: 99%
“…Studies exploring the relationship between trauma exposure and suicide risk among NK refugee women are limited. However, a few previous studies with other refugee populations have shown that higher levels of trauma can increase suicide risk (Ellis et al, 2015;Geirsdottir et al, 2021;Meyerhoff et al, 2018). According to the ITS (Joiner, 2005;Van Orden et al, 2010), not every individual with suicidal ideation acts on their suicidal thoughts.…”
Section: Exposure To Trauma and Suicide Riskmentioning
confidence: 99%
“…Refugees are likely to experience traumatizing events both in their home country, during their migration, and after arrival (Khan Amiri, et al, 2021). Nevertheless, refugees were in general not found to have higher suicide rates when compared to the general population in Denmark, Norway and Sweden (Khan Amiri, et al, 2021, Geirsdottir, et al, 2021, Amin, et al, 2021a, Amin, et al, 2021b). An exception is unaccompanied minors who seek asylum; this group was found to have higher suicide rates when compared to youth in Sweden (Mittendorfer -Rutz, et al, 2020).…”
Section: Stressful Life-eventsmentioning
confidence: 99%
“…Suicide accounts for 1.4% of all deaths worldwide and is the fourth leading cause of death between 15-29 years [1]. Suicide attempts are key predictors of future suicide and strongly associated with depression, psychosis, anxiety [2][3][4][5], addictive disorders [6], certain social-demographic factors, including educational level [7,8], and traumatic life events [9]. Risk factors for suicide attempts differ between Eastern and Western countries, with life stress and low social-economic status thought more associated with suicide in Eastern than in Western countries (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for suicide attempts differ between Eastern and Western countries, with life stress and low social-economic status thought more associated with suicide in Eastern than in Western countries (15)(16)(17). However, the difference of suicide attempt between Eastern and Western countries still need to be further explored because most cross-national studies have been conducted in neighbouring countries, such as the Western Paci c Region or Europe [7,[10][11][12]. Cross-national studies carried out in very different cultural settings may help in providing more comprehensive understanding of etiological mechanisms to aid policy-making for prevention, and also whether the same principles apply globally [13].…”
Section: Introductionmentioning
confidence: 99%